Bilingual Science Lexicon of Pre-Serviced Primary School Teachers - Magdalena López-Pérez; Juan Luis de la Montaña Conchiña; José Luis Bravo Galán; Guadalupe de la Maya Retamar (MDPI AG, 2023)
Bilingual teaching has experienced rapid growth in the Spanish educational panorama and numerous university programmes have emerged with the aim of training future CLIL (Content and Language Integrated Learning) teachers. However, there is little research assessing the level of linguistic competence in Spanish and foreign languages of future teachers, especially those who are studying for a bilingual degree. Although this work is part of a broader project that analyses bilingual lexical competence in subjects related to the Social Sciences and Experimental Sciences, we focus on the analysis of lexical availability of content related to the teaching of science. The sample consisted of 46 students of the Degree in Primary Education at the University of Extremadura. Using a lexical availability test, lexical production in Spanish and English is analysed and compared to determine whether the fact of studying in English affects the acquisition and consolidation of lexical knowledge in Spanish. The results show that there are no significant differences in lexical production between Spanish and English. In addition to the quantitative data, results from the qualitative analysis are presented, analysing the most available words and the organisation of the lexicon in both languages.